Van, Turkey earthquake of 23 october 2011, mw 7.2; an overview on disaster management. - Mehdi Zaré; Behnaz Nazmazar (Tehran University of Medical Sciences, 2013)
An earthquake was happened on 23 October 2011 in Van, Turkey (Mw7.2) at the eastern most area of Anatolian plateau and in the neighborhood of Iranian border (West Azerbaijan Province). The study was performed based on field and office observations and has been focused on the process of disaster management in Turkey after the 23 October 2011 earthquake. We surveyed the quake from the view point of disaster management, and study the relief process during and after the catastrophe. The day-to-day disaster management procedure in seventeen days after the event has been scrutinized as well. The number of victims and extent of damage in Van earthquake was relatively limited according to the national experiences and recent modernization of infrastructures in Turkey. The Van earthquake caused 644 deaths and demolishing of several buildings in the cities of Van and Erciş in Van Province. The performance of the government organizations is however criticized based on their response to the event.